Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Apoteker Yang Bekerja di Apotek di Kota Padang - Djamaan, Akmal; Syahrul, Laura; Bakhtra, Dwi Dinni Aulia (Fakultas Farmasi Universitas Andalas, 2013)
Humans resources must be evaluated as a key factor in an organizations success. Humans resource organization has a wide range of needs. Job satisfaction is a reflection of the employees attitude towards the overall feeling of the work, it consists of various aspects. Job satisfaction can improve service quality and increase employee satisfaction. This was a descriptive study about pharmacists who work at a pharmacy in Padang city as much as 50 respondent. There are six variables that influence job satisfaction of pharmacists: working conditions, salary, promotion, fair treatment, job security, relationships with co-workers and the relationship with the leader. Results showed that the pharmacists working at pharmacies in Padang was just quite satisfied with the work. There was a variable relationship between co-workers and the job satisfaction of the respondents in the amount of 76.32%. Total achievements of the respondents to the relationship with the fair treatment of 75.76 %, 75.68% working conditions, relations with the leaders of 73.92%, 72.79% salary and promotion. Variables of job security less the total respondents 59.80% achievement . Differences in demographic factors also affect the job satisfaction of the respondents. Job satisfaction of male respondents are influenced by working conditions, while the female respondents are affected by fair treatment and relationships with co-workers. Respondents who have a service life over 5 years shows that work satisfaction is strongly influenced by the variable of fair treatment while his tenure of 1 to 5 years are affected by working conditions. Respondents who have over 30 years of age are affected by work satisfaction and working conditions for the age 24 to 30 years of work satisfaction is strongly influenced by fair treatment.